An exploratory study of an organisational strategy and organisational structure using the miles and snow typology : a case for a national government department - Vilakazi, Nhlanhla (Publisher: Stellenbosch : Stellenbosch University, 2023)
Thesis (MPA)--Stellenbosch University, 2023.